Ni–Bi–Zn ternary system investigation using diffusion couples technique - Gandova, Vanya Desimirova (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
Investigation of Ni-Bi-Zn system was performed by diffusion couples technique and diffusion paths were constructed. For this purpose diffusion couples consisting of solid Ni and liquid Bi-Zn phase were anealing at 450 0C. The phase and chemical compositions of the contact zone were determined by means of scanning electron microscope. It is confirmed that the diffusion layers in Ni-Bi-Zn ternary system were: Beta1, gamma-Ni5Zn21 and liquid. No intermetallic compounds in Bi-Ni binary phase diagram were observed.